Sexual objectification versus empowerment: Examining the effects of sexualized women’s facial expression on viewers’ evaluations of social cognition and self-objectification - Vendemia, Megan A. (Body image, 2024)
Objectification scholarship highlights how traditional media portrayals oftentimes direct attention toward women’s bodies and away from their faces which communicate important social information. This study sought to investigate how thin-ideal, white women’s facial expression potentially attenuates the negative effects of appearing in a sexually objectifying manner using validated imagery. In a 2 × 3 between-subjects experiment (N = 1001 U.S. adult women; Mage = 42.56, SDage = 12.72), portraits of women varied in their sexualization (non-sexualized vs. sexualized) and facial expression (neutral expression, low-intensity smiling, high-intensity smiling) to better understand how these factors influence dimensions of social cognition (competence, warmth, authenticity), self-promotional attributions, and viewers’ own self-objectification. Results revealed that viewers rated sexualized (vs. non-sexualized) women lower in competence and authenticity, as well ascribed more self-promotional explanations for their behavior. Moreover, exposure to sexualized women heightened viewers’ self-objectification, regardless of facial expression. Results also indicated that smiling intensity positively influenced viewers’ ratings of social cognition. However, there is little evidence that smiling intensity overrides the negative effects of sexualization. Implications for the sexual objectification of women are discussed. •An experiment examined how sexualization and facial expression affect social judgments.•Sexualized (vs. non-sexualized) women were judged more harshly by other women.•Smiling intensity positively influenced viewers’ ratings of social cognition.•Sexualized women heightened viewers’ self-objectification, regardless of facial expression.